Anatomical and Immunohistochemical Variations Regarding the Epidermal Stem Cell among Different Traumatic Fingers of Hands in Iraqi Male Workers - Hatem A Hatem1 , Ahmed S. Mazyon2 , Hala Mohammed Majeed3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The role of stem cell during the whole life of human constricted into two stages. First stage occurred during prenatal life when stem cell take part in formation of organ in process called embryogenesis. Second stage occurred in postnatal life when these cells contribute in regeneration of damaged or old tissue as repairing or substituting cell in adults. Patient and Method: 150 male volunteers who work in different industries with traumatic finger of the right or left hand (33 right thumb,25 right middle finger ,22 right little finger,28 left thumb,26 left middle fingers 16 left little finger) were taken on from the Department of surgery, Baghdad Hospital, Baghdad; Iraq from February 2019 to October 2019. Results: Anatomical results showing that The grip was affected only in case of traumatic thumb. Vimentin rich-stem cells were highly positive in the proximal epidermal areas of traumatic fingers more than the stem cells in the distal areas of the same fingers. Conclusion: there is a little hope in the near future that the injured or even amputated finger or any part of the body could be replaced by new one made by culturing stem cells in laboratories.